ANALISA LUASAN LUBANG VENTILASI FACADE TERHADAP LUASAN LANTAI - ., Mufidah; Murti, Farida; Bintarjo DH, Benny; Pratama, Hanny Chandra; Tri Putranto, Yunantyo (JHP17 (Jurnal Hasil Penelitian), 2016)
Flat development is a response for citizen dwelling needs, especially for the citizen who have a lower economic, problem of lands high cost, and limited lands. Based for the problem, The Indonesian government has made a policy to built rental flats or belonging flats as a solution. On the flat development, one of criteria should applied is facade of a flat which can reduce heat thermal into buildings. This study is a second part which made a recommendation of flat mass to get comfortable thermal value by natural energy. While, this second study for identify a design recommendation of flat facade to get comfortable thermal value by natural energy. This method of study uses some literatures related on arranger a facade on the flats. The correlate variable is about materials and ventilation. Ventilation is about wide, position, and model of ventilation on the building. Besides that, explore the facade and analyze based for land efficiency, occupant’s behavior, building aesthetics, wind flow optimizing, sunlight optimizing and heat insulation into building. Result of this study is get a saving energy flat model on warm-humid climate. Focus on optimize the facade of the buildings to get comfortable value for the occupants.Keywords: flat facade, energy saving, warm-humid climate